1991
DOI: 10.1002/ijc.2910480603
|View full text |Cite
|
Sign up to set email alerts
|

Early‐age body size, adult weight gain and endometrial cancer risk

Abstract: To further characterize the association of obesity and endometrial cancer, in particular with regard to the role of early-age obesity and adult weight gain, the authors assembled by computer linkage a population-based historical cohort of 30,266 women born between 1913 and 1932, for whom weight and height had been recorded in 1942-43 and 1972. Linkage of this cohort to the Hawaii Tumor Registry resulted in the identification of 214 (mainly post-menopausal) incident cases of endometrial cancer for 1972-1986. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
37
1
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 23 publications
10
37
1
1
Order By: Relevance
“…Some misclassification of disease site may have occurred but would have been more likely to attenuate than spuriously to create associations. Finally, the validity of our record linkage procedure and the quality of our population database have been demonstrated, z, 8 In summary, the present study provides further evidence for an association of obesity with colon cancer in men and suggests that this association is limited to the sigmoid colon and is related to both early and late events of colon carcinogenesis.…”
Section: Discussionmentioning
confidence: 66%
“…Some misclassification of disease site may have occurred but would have been more likely to attenuate than spuriously to create associations. Finally, the validity of our record linkage procedure and the quality of our population database have been demonstrated, z, 8 In summary, the present study provides further evidence for an association of obesity with colon cancer in men and suggests that this association is limited to the sigmoid colon and is related to both early and late events of colon carcinogenesis.…”
Section: Discussionmentioning
confidence: 66%
“…Our findings regarding BMI at age 18 years are consistent with data from the remaining studies (21,(24)(25)(26) reporting that the association with early age BMI is either no longer statistically significant (24)(25)(26) or null (21) after adjustment for baseline BMI. Additional four studies (7,9,19,22) showed a nonsignificant positive association, but those studies did not adjust for current BMI.…”
Section: Bmi At Different Life Stages and Endometrial Cancermentioning
confidence: 96%
“…Several studies reported a statistically significant (7,9,10,12,(19)(20)(21) or marginally significant (22) positive relation between adult weight gain and endometrial cancer risk, showing a 2-to 6-fold increased risk with increasing level of weight gain. Adult weight gain has not always been consistently defined in these studies but has generally encompassed weight gain from age 18 years to current ages.…”
Section: Cancer Epidemiol Biomarkers Prev 2007;16(4) April 2007mentioning
confidence: 99%
“…1 Expanding knowledge of the importance of exposures throughout the life course 2 has encouraged investigations of relationships between preadult body mass index (BMI) and later cancer risk. [3][4][5][6][7][8][9] With rising levels of childhood adiposity evident in the developed world, 10,11 a clear understanding of the long-term impact on adult health is crucial. As obese children tend to become obese adults, 12 the prevention of overweight in childhood may minimise obesity-related disease in adulthood.…”
mentioning
confidence: 99%